Der blev indviet en synagoge i Krystalgade i 1833...på Sankt Thomas! Jøderne i Dansk Vestindien til 1917 - N. Christensen, Merete (Rambam. Tidsskrift for jødisk kultur og forskning, 2021)
The article provides an overview of the history of Danish Jews in the Danish West Indies. It begins with a brief history of the Danish West Indies. Denmark- Norway owned three islands: Saint Thomas, Saint Jan, and Saint Croix. There was an excellent natural harbor on Saint Thomas, and here the city of Charlotte Amalie prospered. In the 1830s, the city had over ten thousand inhabitants. The most important commodity in the Danish West Indies was sugar which was made and sold in Denmark- Norway, Europe, and North America. The Danish West Indies were also the home of prominent as well as more obscure Jews. A famous example is the governor Gabriel Milan who came to Saint Thomas with his family in the late 17th century. His religious affiliation has been the subject of speculation and investigation. He was sent back to Denmark charged with misconduct and executed by hanging after having served only a couple of years on Saint Thomas. Jews on Saint Thomas were free to practice their religion in private. In the late 18th century they applied for permission to build a synagogue, which was granted. At that time, a burial ground had already been established, and it still exists today. Up until the 1830s, Jews on Saint Thomas were Sephardic, but throughout the 1830s Ashkenazic Jews also arrived to the island. In 1831 a fire destroyed the greater part of Charlotte Amalie including the synagogue. However, the Jewish community on Saint Thomas was renowned and well-reputed, and soon money for the reestablishment of the synagogue was raised. The Jewish community on Saint Thomas was fully integrated in the Danish colonial society. Jewish confirmations were held, and the Jewish schools were popular even among Christians. The community was an example to other Jewish communities in the USA. It was a democratic community where women participated in services on equal terms. Over the years several well-known rabbis lived on Saint Thomas, and in 1830 the famous painter Camille Pissarro was born.